(untitled) (New Jersey, 2002)
This book deals with the broad spectrum of nanoscience and nanotechnology, where interdisciplinary collaboration is essential. Focuses are placed on materials (nanoparticles, dendrimer, CNT), fabrication (LB film, SAM, alternative adsorption, microcontact printing, photofabrication) and characterization (scanning probe microscopy and electron microscopy) on the nanoscale. Emerging applications to nanophotonics and nanobionics are discussed as well.
Keywords: Nanotechnology,Công nghệ NANO; Congress,Hội thảo